2016
DOI: 10.1176/appi.focus.140201
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Seven Psychotherapeutic Interventions for Patients with Depression: A Network Meta-Analysis

Abstract: Background: Previous meta-analyses comparing the efficacy of psychotherapeutic interventions for depression were clouded by a limited number of within-study treatment comparisons. This study used network meta-analysis, a novel methodological approach that integrates direct and indirect evidence from randomised controlled studies, to re-examine the comparative efficacy of seven psychotherapeutic interventions for adult depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
219
1
20

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(251 citation statements)
references
References 48 publications
11
219
1
20
Order By: Relevance
“…In a large RCT, Elkin et al (1989) found that IPT is equally effective to medication and CBT, with some evidence for increased efficacy of IPT for severely depressed patients. There is also preliminary evidence suggesting the superiority of IPT over alternative psychotherapies (Cuijpers et al 2008(Cuijpers et al , 2011, specifically supportive counselling (Barth et al 2013) and CBT (de Mello et al 2005).…”
Section: Interpersonal Therapy (Ipt)mentioning
confidence: 99%
See 1 more Smart Citation
“…In a large RCT, Elkin et al (1989) found that IPT is equally effective to medication and CBT, with some evidence for increased efficacy of IPT for severely depressed patients. There is also preliminary evidence suggesting the superiority of IPT over alternative psychotherapies (Cuijpers et al 2008(Cuijpers et al , 2011, specifically supportive counselling (Barth et al 2013) and CBT (de Mello et al 2005).…”
Section: Interpersonal Therapy (Ipt)mentioning
confidence: 99%
“…Despite the heated debate regarding the superiority of one treatment over others, there is fairly wide acceptance of the 'Dodo Bird Verdict ' (Luborsky et al 1975), at least in the case of depression, suggesting that all treatments are more or less equally effective (Cuijpers et al 2008;Barth et al 2013). Furthermore, research in the past two decades has taught us that psychotherapeutic treatments of depression are superior to waitlist and other control conditions (Barth et al 2013;Lambert, 2013), and that psychotherapy combined with anti-depressant medication is more effective than medication alone (Barber et al 2013;Köhler et al 2013;Hollon et al 2014;Fonagy, 2015;Leichsenring et al 2015). There is also evidence suggesting that some types of psychotherapies are not only as effective as medication, but also have higher long-term enduring effects (Hollon & Ponniah, 2010;Cuijpers et al 2013b).…”
mentioning
confidence: 99%
“…For example, one meta-analysis suggests only a 12-16% response rate to antidepressants in individuals with moderate to severe depressive symptoms with a slight improvement with the addition of other therapeutic modalities, such as cognitive-behavioral therapy [38]. Other studies have revealed that only 22% of individuals with moderate-severe symptoms receive adequate treatment11 and the majority of those treated with UC experience recurrences and/or discontinue treatment before achieving remission or response [3,[39][40][41].These findings underscore the need for additional, more acceptable and effective therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Depressive symptoms are projected to be a leading cause of illness and disability in the world by 2030 [2,3].Nearly 20% of pregnant women experience depressive symptoms and 13% of pregnant women experience chronic, recurrent symptoms Of this large number of women experiencing depressive symptoms during pregnancy, the majority are experiencing depression as a chronic condition, rather than a new-onset occurrence [4][5][6][7]. Due to the often protracted, disabling nature of the symptom experience the adverse effects of depressive symptoms can significantly impact the mother as symptoms are associated with increased risk for poor adherence to prenatal care, preterm birth, suicide, substance abuse, and postpartum depression [4,[8][9][10][11][12][13][14][15].…”
mentioning
confidence: 99%
“…[1,2] Moreover, increasing evidence accumulated over the past 10 years has led many evidence-based psychotherapies (EBPs)-psychotherapies validated in randomized controlled trials-to be recommended at the highest level and as first-line treatments in clinical practice guidelines. In addition, increasing research over the past decade has demonstrated EBPs to be at least as effective as medications and for some conditions to be more effective and enduring.…”
mentioning
confidence: 99%